PENGARUH KONDISI HIDROGEOLOGI DAN SANITASI LINGKUNGAN TERHADAP TINGKAT KANDUNGAN BAKTERI âCOLIâ PADA AIRTANAH DANGKAL TAHUN 2012 DI KOTA YOGYAKARTA - , YOGY PRASETYO K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The level of contamination in shallow groundwater can indicate the state of health in some district, especially an area that has a population. Groundwater contamination follow up the level of development and increasing of population density. Some failure waste management can make contamination in groundwater, which may affect either directly or indirectly to the quality of the local environment. One of groundwater pollution is coli bacteria. This study aimed to determine the level of coli bacterial contamination on shallow groundwater in Yogyakarta City and its surrounding, which is from all of groundwater sample contain coli bacteria, then both spatial and statistical analysis of the factors that influence the level of coli bacteria. Factors which affecting the level of coli bacteria in shallow groundwater in Yogyakarta City and its surrounding, are divided into two factors, the first is hydrogeological conditions and the second is environmental sanitation. Both of these factors analyzed using spatial analysis and statistics analysis. The main task in spatial analysis is overlapping some map which is the level of coli bacteria map with the other maps from those factors. Statistical analysis were performed by grouping and reduce the factors that influence the levels of coli bacteria, with cluster analysis and factor analysis. Based on the spatial analysis , the factors that influence the levels of coli bacteria in shallow groundwater in Yogyakarta City and its surrounding are groundwater level, groundwater depth and sewage systems. Based on statistical analysis, the result from cluster analysis are the study area divided into 2 clusters or groups, which cluster 1 has a groundwater situation much better than the cluster 2. The result from factor analysis produces some factors that influence the levels of coli bacteria are gradient of groundwater level, groundwater depth, groundwater velocity and sewage systems.